2011
DOI: 10.1113/expphysiol.2010.055483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training and detraining on monocarboxylate transporter (MCT) 1 and MCT4 in Thoroughbred horses

Abstract: The aim of this study was to investigate the effects of training and detraining on the monocarboxylate transporter (MCT) 1 and MCT4 levels in the gluteus medius muscle of Thoroughbred horses. Twelve Thoroughbred horses were used for the analysis. For 18 weeks, all the horses underwent high-intensity training (HIT), with running at 90-110% maximal oxygen consumption (V O 2 max ) for 3 min, 5 days week −1 . Thereafter, the horses either underwent detraining for 6 weeks by either 3 min of moderate-intensity train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 45 publications
(59 reference statements)
0
51
0
Order By: Relevance
“…Previous studies showed that MCT1 is increased by the most type of training, while sprint and strength training can up-regulate MCT4 expression [12]. Interestingly, we have previously found that increased MCT4 by high-intensity training could not be maintained by moderate-intensity training in horses [21]. However, it remains a challenge to understand the mechanisms determining which factor affects the expression of MCTs.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies showed that MCT1 is increased by the most type of training, while sprint and strength training can up-regulate MCT4 expression [12]. Interestingly, we have previously found that increased MCT4 by high-intensity training could not be maintained by moderate-intensity training in horses [21]. However, it remains a challenge to understand the mechanisms determining which factor affects the expression of MCTs.…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, the physiological importance of the phenomenon is unclear. It has been shown that the amount of MCTs in muscle has been increased by training in horses (Kitaoka et al, 2011) and thus it is important for physiological capacity. It can be speculated, however, that LTA in RBC must also be beneficial, because it has surveyed evolution and breeding.…”
Section: Introductionmentioning
confidence: 99%
“…This is where the previous research on monocarbolylate transporters becomes more interesting (Juel, 1997), to which the data of Kitaoka et al (2011) form the most recent contribution. The increased density of monocarboxylate transport proteins 1 and 4 (MCT1 and MCT4) after intense exercise training in the horse (Kitaoka et al 2011) is logical to the need to sustain muscle lactate production during intense exercise. The rapid and high capacity for lactate removal is essential to minimize muscle lactate accumulation or, alternatively, to prolong the time and increase the metabolic flux to attain a given muscle lactate accumulation.…”
mentioning
confidence: 95%